Application of Deaf Space in the Interior of Creativity and Art Center for the Deaf - Aurelius, Alexia; Rachmayanti, Ika; Fajarwati, Ade Ariyani Sari (Institut Seni Indonesia Denpasar, 2024)
Deaf people have difficulty or cannot even hear, so they develop sign language to communicate. Difficulty of hearing and communication differences prevent deaf peo-ple from learning. However, the potential and talent of each deaf person are the same as those of other hearing people. From this point of view, deaf people can continue to work in the field of art that prioritizes form, visuals, and movement or motor skills that do not require the sense of hearing. By being creative, deaf people can voice their opinions and provide messages and stories for people who enjoy their work. This study aims to give awareness to the public and opportunities for deaf people to get space and facilities to be creative. The method used in this study is qualitative analy-sis and design thinking method. The design facilitates creative and artistic activities as outlined in the exhibition room for deaf works, painting, drawing, makerspace, deaf theater practice, multipurpose room, classroom, mini library, and co-working space ensuring that deaf people are comfortable doing activities in the room. This research was developed for the community to provide opportunities for deaf people to be more accessible and dare to be creative.